2012
DOI: 10.4236/as.2012.35079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trinexapac-Ethyl on different wheat varieties under desert conditions of Mexico

Abstract: A field study was conducted to determine the effect of Trinexapac-Ethyl (TE) on four wheat varieties (Rafi C97, Altar C84, Nacori C97 and Rayon F86) at three growth stages (first node, second node and flag leaf). TE application (150 g a.i. ha<sup>-1</sup>) reduced plant height and decreased grain yield at any growth stage. Yield decrease was associated to a significant reduction in the number of grains per spike and in grain weight. TE delayed flowering time and grain maturity, while stem diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
2
8
1
1
Order By: Relevance
“…The GS29-Half treatment reduced yield the least in Blackstone and was still 16% less than untreated barley. Grijalva-Contreras et al (2012) observed grain yield decreases in wheat up to 13%, but only with greater TE rates than tested in this study (14.4 fl oz TE acre −1 ). Grain yield was significantly decreased by 41-42% in Holland following all treatments with TE application at GS32, compared to the check.…”
Section: Effect Of Plant Growth Regulator On Grain Parameterscontrasting
confidence: 41%
“…The GS29-Half treatment reduced yield the least in Blackstone and was still 16% less than untreated barley. Grijalva-Contreras et al (2012) observed grain yield decreases in wheat up to 13%, but only with greater TE rates than tested in this study (14.4 fl oz TE acre −1 ). Grain yield was significantly decreased by 41-42% in Holland following all treatments with TE application at GS32, compared to the check.…”
Section: Effect Of Plant Growth Regulator On Grain Parameterscontrasting
confidence: 41%
“…Reports by Grijalva‐Contreras et al. (2012) and Zhang et al. (2017) indicate the application of TE may even reduce grain yield in a semidwarf wheat cultivar.…”
Section: Resultsmentioning
confidence: 97%
“…Initially, we observed a positive response for yield for Flourish at Lethbridge (data not shown); however, a cultivar × TE interaction was eventually detected with the accumulation of additional site-years and was largely the result of a lack of yield response to TE when applied to Flourish (Figure 3). Reports by Grijalva-Contreras et al (2012) and Zhang et al (2017) indicate the application of TE may even reduce grain yield in a semidwarf wheat cultivar. In a semidwarf or reduced height cultivar, reductions in canopy height caused by TE applications could possibly interfere with light interception and canopy gas exchange, which might result in lower biomass production and grain yield (Gent, 1995).…”
Section: Crop Sciencementioning
confidence: 99%
“…Days to maturity were increased for three out of four of those comparisons. Previous studies have shown delays in wheat maturity with trinexapac, although scale of effect was dependent on rate and timing of application (Wiersma et al 2011;Grijalva-Contreras et al 2012).…”
Section: Days To Maturitymentioning
confidence: 96%